Development and initial validation of the Team Mental Models Instrument (TMMI): A psychometric tool to measure shared and complementary mental models in sports. (July 2022) - Filho, Edson; Rettig, Jean; Gaspar, Pedro; Bagni, Guilherme
Abstract: Objectives: To develop and validate a new psychometric tool to measure Shared Mental Models (SMM) and Complementary Mental Models (CMM) in sport settings, namely the Team Mental Models Instrument (TMMI). Methods: Data from 627 college athletes competing in the European Universities Games 2018 was randomly organized into two sub-samples. Data from Sub-Sample 1 (n = 320) was used to conduct a hierarchical confirmatory factor analysis (H-CFA) to examine the construct validity of the TMMI. Sub-Sample 2 (n = 307) was used to examine the discriminant, convergent, and nomological validity of the TMMI, with respect to social and task cohesion and team performance. Results: A preliminary TMMI with 60 items, 30 items each for the SMM and CMM sub-dimensions, was subjected to H-CFA based on data from Sub-Sample 1. Results of this analysis confirmed the construct validity of an 11-item TMMI, with the two hypothesized reflective indicators, SMM (four items) and CMM (seven items). Correlational and structural equation modelling analysis was used to analyze data from Sub-Sample 2, with the results confirming the discriminant, convergent, and nomological validity of the TMMI. Conclusion: Our analysis supports the theorization that the concept of Team Mental Models is underpinned by two dimensions, namely SMM and CMM. This instrument can be used as an applied tool to inform interventions aimed at developing team dynamics in general, and team cognition in particular. Scholars can use the TMMI to study the linkage between TMM and other key team processes. Highlights: Our findings support the notion that team mental models is a multidimensional concept. The TMMI is an 11-item tool that measures shared and complementary mental models. The TMMI was found to be related to cohesion and to predict team performance. The TMMI captures teammates shared and complementary knowledge of "what to do". The TMMI captures teammates shared and complementary knowledge of "how to do".